KEMAMPUAN BERPIKIR ANALITIS DALAM PENDIDIKAN KIMIA MELALUI STEM-PJBL: TINJAUAN LITERATUR - Sari, Nur Indah (MACCA : Science-Edu Journal, 2025)
The project learning model is an innovative model that is ideal for developing essential 21st century skills. This study aims to investigate the development, implementation, and integration of STEM-PjBL with students' analytical thinking skills through a literature review. The research method is a systematic literature review of 10 articles that have met the inclusion and exclusion criteria. The review method involves analyzing research trends and pedagogical approaches to analytical thinking skills, developing thinking skills through STEM-PjBL, and 3. Integration of Design Thinking in STEM-PjBL. The results show the potential of STEM-PjBL to effectively improve analytical and critical thinking skills in chemistry education. Educators can maximize the potential of STEM-PjBL by implementing the right pedagogical approach and overcoming existing challenges. Integration of design thinking can optimize the development of students' thinking skills to solve problems creatively and innovatively. Thus, the application of STEM-PjBL and integration of design thinking are effective strategies to improve the quality of chemistry learning and prepare students to face the challenges of the 21st century.